2018
DOI: 10.2340/16501977-2292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postsurgical rehabilitation programmes in patients operated for lung cancer: A systematic review and meta-analysis

Abstract: Objective: To review the evidence concerning the effects of postoperative exercise interventions on exercise capacity and health-related quality of life following resection for non-small cell lung cancer, and to review whether different initiation times of exercise produce different effects on exercise capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 37 publications
0
44
0
2
Order By: Relevance
“…Seven systematic reviews (eight references as one systematic review was published in duplicate) were included in this overview. Six of the seven reviews included meta‐analyses (Cavalheri et al, 2019; Cavalheri & Granger, 2017; Cavalheri et al, 2013a; Li et al, 2017; Mainini et al, 2016; Rosero et al, 2019; Sommer et al, 2018). One review (Cavalheri et al, 2019) is an updated version of the old one (Cavalheri et al, 2013a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven systematic reviews (eight references as one systematic review was published in duplicate) were included in this overview. Six of the seven reviews included meta‐analyses (Cavalheri et al, 2019; Cavalheri & Granger, 2017; Cavalheri et al, 2013a; Li et al, 2017; Mainini et al, 2016; Rosero et al, 2019; Sommer et al, 2018). One review (Cavalheri et al, 2019) is an updated version of the old one (Cavalheri et al, 2013a).…”
Section: Resultsmentioning
confidence: 99%
“…The effects on exercise capacity were examined in all six metaanalyses ( Table 2). Three reviews (Cavalheri et al, 2019;Cavalheri et al, 2013a;Sommer et al, 2018) reported significantly increased exercise capacity after postoperative exercise interventions. One review (Li et al, 2017) Two reviews (Cavalheri & Granger, 2017;Rosero et al, 2019) reported statistically significant increases in exercise capacity…”
Section: Exercise Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…[28][29][30][31] Rehabilitation and exercise interventions reduce the negative impact of treatment-related symptoms and improve function of individuals living with and beyond cancer. [32][33][34][35][36][37][38][39][40][41][42] Despite growing evidence and recommendations for better integration of rehabilitation into oncology care, [43][44][45][46] rehabilitation is a relatively underutilized service. [47][48][49][50] This care gap is well characterized internationally and contributes to a growing morbidity burden as the population of cancer survivors continues to increase.…”
Section: Introductionmentioning
confidence: 99%